2020
DOI: 10.3390/nu12020477
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Shiitake Mushroom-Derived Exosome-Like Nanoparticles in D-Galactosamine and Lipopolysaccharide-Induced Acute Liver Injury in Mice

Abstract: Fulminant hepatic failure (FHF) is a rare, life-threatening liver disease with a poor prognosis. Administration of D-galactosamine (GalN) and lipopolysaccharide (LPS) triggers acute liver injury in mice, simulating many clinical features of FHF in humans; therefore, this disease model is often used to investigate potential therapeutic interventions to treat FHF. Recently, suppression of the nucleotide-binding domain and leucine-rich repeat related (NLR) family, pyrin domain containing 3 (NLRP3) inflammasome, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 54 publications
(96 reference statements)
1
67
0
Order By: Relevance
“…Since GDNs blocked the assembly and activation of NLRP3 inflammasome, these NVs represent a new promising class of NLRP3 inflammasome inhibitors. Exosome-like nanoparticles from six mushrooms presented various effects on the NLRP3 inflammasome in BMDM [42]. Interestingly, NVs from Shiitake mushrooms (SMNs), at a concentration range Wheat grass WDNs promote proliferation and exert anti-apoptotic effects on HDF (primary human dermal fibroblasts), HUVEC (human endothelial vascular endothelial cells), and HaCaT (human keratinocytes), induce tube branching in HUVEC, and increase collagen type I expression in HaCaT as both protein and mRNA [69] BMDCs: bone marrow-derived dendritic cells; BMDM: bone marrow-derived macrophages; HO-1: heme oxygenase-1; IL: interleukin; Nrf2: nuclear factor (erythroid-derived 2)-like 2; NVs: nanovesicles; LPS: lipopolysaccharide; ROS: reactive oxygen species; TNF: tumor necrosis factor.…”
Section: Anti-oxidant Anti-inflammatory and Regenerative Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since GDNs blocked the assembly and activation of NLRP3 inflammasome, these NVs represent a new promising class of NLRP3 inflammasome inhibitors. Exosome-like nanoparticles from six mushrooms presented various effects on the NLRP3 inflammasome in BMDM [42]. Interestingly, NVs from Shiitake mushrooms (SMNs), at a concentration range Wheat grass WDNs promote proliferation and exert anti-apoptotic effects on HDF (primary human dermal fibroblasts), HUVEC (human endothelial vascular endothelial cells), and HaCaT (human keratinocytes), induce tube branching in HUVEC, and increase collagen type I expression in HaCaT as both protein and mRNA [69] BMDCs: bone marrow-derived dendritic cells; BMDM: bone marrow-derived macrophages; HO-1: heme oxygenase-1; IL: interleukin; Nrf2: nuclear factor (erythroid-derived 2)-like 2; NVs: nanovesicles; LPS: lipopolysaccharide; ROS: reactive oxygen species; TNF: tumor necrosis factor.…”
Section: Anti-oxidant Anti-inflammatory and Regenerative Activitiesmentioning
confidence: 99%
“…In alternative to weighing, the yield of PDNVs can be measured by a zeta-sizer. For instance, among the mushrooms tested, oyster mushroom-derived exosome-like nanoparticles had the lowest yield of 2.3 ± 1.5 × 10 11 /g, whereas white button mushroom-derived PDNVs had the highest yield of 8.1 ± 1.6 × 10 11 /g [ 42 ].…”
Section: Isolation and Purification Of Pdnvsmentioning
confidence: 99%
See 1 more Smart Citation
“…They contain metabolites, proteins, lipids, RNAs, miRNAs, mRNAs, and DNAs and can transfer their cargo to recipient cells, playing a fundamental role as extracellular messengers to mediate cell–cell communication [ 3 ]. The critical role played by EVs in the mediation of cell–cell communication has been identified both in health and disease and in bacterial, fungal, and animal kingdoms [ 4 , 5 , 6 , 7 , 8 ]. An increasing number of studies have shown the existence of plant-derived nanosized particles, the characteristics of which resemble those of mammalian exosomes [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, exosomes are nanometer-sized vesicles in a range of 30-100 nm, present in many biological fluids of different organisms [3]. Previous studies have identified and reported the existence of exosome-like nanoparticles (ELNs) in plants [4], fruits [5], and very recently also in mushrooms [6].…”
Section: Introductionmentioning
confidence: 99%